A 9-year analysis of transoral laser microsurgery (TLM) of head and neck cancer on their potential suitability for transoral robotic surgery (TORS) for estimation of future TORS-specific caseload - Von Scotti, F.; Kapsreiter, M.; Scherl, C.; Iro, Heinrich; Bohr, Christopher (European Review for Medical and Pharmacological Sciences, 2018)
OBJECTIVE: After that the establishment of transoral robotic surgery (TORS) for head and neck cancer has been adopted in North America, it has also recently been adopted in Europe. In these parts, transoral laser microsurgery (TLM) is widely applied. The aim of the study was to identify the absolute number of operations amenable to TORS at a TORS initiating institution on the basis of all former TLM cases. PATIENTS AND METHODS: All laser surgery procedures from May 2004 to April 2013 (108 months) were initially retrospectively registered; after that, all stage pT1 and pT2 squamous cell carcinomas of the oropharynx, hypopharynx, and larynx were selected. RESULTS: Over a period of nine years out of all TLM cases, there were 45 cases of pT1 and pT2 orohypopharyngeal and supraglottic squamous cell carcinomas, which could have been considered for TORS surgery. With the inclusion of a nowadays-typical TORS indication such as tonsil cancer, 142 cases would have been amendable to TORS. CONCLUSIONS: The indication for TORS would have been made in five of the TLM cases per year. Institutions initiating TORS, which own an intensive TLM experience, are encouraged to TORS indications in more than solely typical TLM indications. By indicating TORS instead of handheld surgery, a higher caseload of more than 15 cases per year can be achieved for TORS indications.
EVALuna2:35389